Assessing the level of gender awareness of science teachers: the case of Zimbabwe's two education districts - Chikunda, Charles (Routledge, 2021)
The purpose of the study was to assess the level of gender awareness of science teachers in Zimbabwe's two education districts. A semi-closed questionnaire was administered to a sample of 100 science teachers. The questionnaire assessed teachers' gender awareness based on content, teaching methods, classroom dynamics and their general perception of what is taught as school science. Results show that while some teachers show an appreciable level of gender awareness in their practice, the majority, however, still believe that science is a factual, or objective discipline that is not affected by people's background, culture, attitudes or gender. Inferences from results suggest that there is no systematic effort by teacher education institutions to sensitize teachers on gender issues. The study therefore recommends staff development for practicing teachers as well as mainstreaming gender in the teacher education science curriculum.